THE ROLE OF COMMUNICATIVE METHOD AND CLIL IN DEVELOPING CROSS-CULTURAL COMPETENCE AND EFFECTIVE LANGUAGE ACQUISITION - O. Sh. Uralov (Bright Mind Publishing, 2025)
The methodology of foreign language teaching is a critical pedagogical direction aimed at effectively organizing the language learning process and developing students' linguistic and communicative competence. In modern educational contexts, various methods and approaches are employed to prioritize practical language acquisition. Language learning is not only about mastering a new linguistic system but also understanding the cultural values, worldview, and communication norms of the speakers of that language. The Communicative Approach, which emerged in the 1970s as an alternative to traditional grammar-based methods, emphasizes developing communicative competence. This approach underlines that language cannot be separated from its cultural context, and every word, phrase, or expression is linked to the mentality, values, customs, and social relationships of the community that speaks it. Moreover, the CLIL (Content and Language Integrated Learning) method, developed in the 1990s by David Marsh, combines content learning with language acquisition, facilitating not only linguistic development but also cultural understanding. This paper explores the significance of the communicative method and CLIL in the development of cross-cultural competence, motivating students by using language in real-life contexts, and preparing them for effective global communication.
Keywords: Foreign language teaching, communicative method, CLIL, language acquisition, cross-cultural competence, communicative competence, cultural understanding, real-life contexts, global communication, pedagogical methods.